Evolutionary Programming (EP) for optimal Static Var Compensator sizing in distribution system / Hanem Saad - Saad, Hanem (2007)
This report presents a Evolutionary Programming for optimization and automatic control of reactive power in distribution feeders and substations. An optimal Static Var Compensator placement, sizing, and controlling problem is formulated objecting to minimize power loss in a distribution system. These optimal solutions provide decisions support to reactive power compensation planning in large scale energy companies. The study involved the Evolutionary Programming (EP) Based Technique for Static Var Compensator Placement in Distribution System for loss minimization. Tests were performed on the 12-bus radial distribution system.